TATUS KESEHATAN MENTAL PASIEN GOUT ARHTRITIS DI KOTA TOMOHON - Desi, Desi (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2019)
Gout Arthritis is a disease known as gout, but in certain conditions this disease can cause physicalsymptoms that are not visible to some people. When there are problems with physical health, otherhealth aspects will also have an impact. The same is true for patients diagnosed with Gout Arthritis,not only physical aspects but can affect other aspects, especially when having physical symptoms suchas tofi. Mental health is a condition where there is a balance between emotional, behavioral andcognitive. This is the basis of the importance of maintaining mental health for someone who does nothave physical health problems and for someone who has a disease such as Gout Arthritis patients. Thepurpose of this study was to find out how mental health status in Gout Arthritis patients in TomohonCity. Quantitative research using a descriptive approach was used in this study. Data collection usedsurvey methods with questionnaires. The results showed that the majority of respondents had adequatemental health (80.6%). Based on the results of the study, it was concluded that mental health status inGout Arthritis patients in Tomohon City was at a sufficient level. These influenced by himself and theenvironment around them.